Connected backyard gardening as a platform for suburban community building in Adelaide, Australia. Issue 1 (1st January 2022) - Suh, Jungho; Auberson, Laura; Ede, Sharon
ABSTRACT: In a connected backyard gardening scheme, the backyards of neighboring houses are connected through mutually accessible gates so that the individual households can benefit from the sharing of resources, and develop social links with neighbors. This study highlights the significance of connected backyard gardening in terms of community building, based on interviews with a group of five households and a group of three households from two suburban streets in Adelaide, Australia. The study has found that these connected backyard gardens are a new form of intentional communities. They have demonstrated it is possible to carry out a sharing economy, a circular economy, and a platform economy in a small scale yet collective and innovative manner. The spread of connected backyard gardening in Adelaide is being challenged by land-subdivision pressure favoring urban infill. The study suggests the social benefits of collective residential gardening should be factored into city planning.